2005
DOI: 10.1038/sj.ijo.0803014
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor α-mediated adiposity-lowering and hypocholesterolemic actions of the selective estrogen receptor modulator acolbifene

Abstract: OBJECTIVE:The selective estrogen receptor (ER) modulator (SERM) acolbifene (ACOL), a potent and pure antiestrogen in the mammary gland and uterus, exerts beneficial pro-estrogenic actions on energy balance, insulin sensitivity and lipid metabolism. ACOL binds ERs a and b, both of which have been involved in the metabolic actions of estrogen. This study aimed at determining the identity of the ER involved in the beneficial metabolic actions of ACOL. DESIGN AND MEASUREMENTS: ACOL was administered for 4 weeks to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
(65 reference statements)
0
20
1
Order By: Relevance
“…Although sex-and depot-related differences in ERα and ERβ have been reported (Pedersen et al 1991, Blouin et al 2009), E2-deficient mouse models indicate that E2 is important for lipid homeostasis and adipocyte lipolytic/lipogenic activity in both sexes (Heine et al 2000, Jones et al 2001. A study that administered a potent anti-estrogen, acolbifene, to mice demonstrated that both males and females developed decreased WAT mass and circulating cholesterol (Lemieux et al 2005). Although studies in rodents support similar WAT responses in males and females to direct E2 stimulation at classical ERs (Heine et al 2000, Jones et al 2001, other evidence supports a heterogenous response to E2, particularly in the context of obesity.…”
Section: Lipolysis and Lipogenesismentioning
confidence: 95%
“…Although sex-and depot-related differences in ERα and ERβ have been reported (Pedersen et al 1991, Blouin et al 2009), E2-deficient mouse models indicate that E2 is important for lipid homeostasis and adipocyte lipolytic/lipogenic activity in both sexes (Heine et al 2000, Jones et al 2001. A study that administered a potent anti-estrogen, acolbifene, to mice demonstrated that both males and females developed decreased WAT mass and circulating cholesterol (Lemieux et al 2005). Although studies in rodents support similar WAT responses in males and females to direct E2 stimulation at classical ERs (Heine et al 2000, Jones et al 2001, other evidence supports a heterogenous response to E2, particularly in the context of obesity.…”
Section: Lipolysis and Lipogenesismentioning
confidence: 95%
“…Ovariectomized (OVX) rats, as well as aromatase, and estrogen receptor knockout mice develop nonalcoholic fatty liver disease (NAFLD), which is characterized by triglyceride accumulation in hepatocytes (hepatic steatosis) (Lemieux et al 2005), one of the most frequent causes of abnormal liver function (Angulo 2002;Browning and Horton 2004). In a recent study that included over 800 women aged 40-59 years, it was confirmed that the menopausal status was indeed associated with hepatic steatosis (Volzke et al 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Although men with ER ␣ mutation developed severe steatosis ( 7 ), the three adult men reported with aromatase defi ciency had impaired lipid metabolism, and only one presented with hepatic steatosis ( 8 ). Aromataseknockout mice ( 3,4 ), ER ␣ -knockout ( ␣ ERKO) mice ( 9 ), and the double ER ␣ and ␤ knockout mice ( 10 ) display elevated triglyceride (TG) levels ( 11 ). These clinical and experimental studies have shown the signifi cant role of the estrogen signaling pathway in lipid homeostasis ( 3,4 ).…”
Section: Human Liver Specimensmentioning
confidence: 99%
“…6A ). In this de novo lipogenesis by [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C-labeling acetic acid procedure, we traced the total radiation that can refl ect the lipogenesis. Acetate is the precursor of lipid synthesis, and fatty acid is the substrate of sterols and lipid synthesis.…”
Section: Molecular Actions Of Estrogen and Androgen In A Rat Brl3a Hementioning
confidence: 99%